روايات الأشعث عن الحسن من خلال السنن الكبرى للبيهقي(جمعاودراسة - قرینات, عبد الحق (University of eloued جامعة الوادي, 2016)
عنوان مذكرتي هو: (روایات الأشعث عن الحسن من خلال السنن الكبرى للبیهقي جمعا ود ا رسة)، والأشعث هو بن عبد الله الحداني من تلامیذ التابعي الجلیل الحسن بن یسار البصري – رحمهما الله -، وقد أخرج الإمام أحمد بن الحسین البیهقي - رحمه الله - في كتابه السنن الكبرى أحادیث یرویها الأشعث عن الحسن، ولذلك سأقوم في هذه الرسالة بجمع هذه الروایات ومحاولة الإحاطة بالطرق والأسانید التي رویت بها قدر الإمكان مع جمع كلام النقاد حولها، بذكر أحكامهم واختلافاتهم والترجیح بینها بما أمكنMy dessertation title is :(Alachaath novels by Alhasan through Asounan Alkobra of Albayhaqi : Collectively and studiously ), And Alachaath is bin Abdallah El Hodani a scholar of the fellow Al Hasan Ibn Yasar Al Basri -may Allah bless them- Also, Imam Ahmed Ibn Al-Hussein Al-Bayhaqi mentioned in his book “Al Sunan Al Kubra” hadiths narrated by Al Ash’ath from Al Hasan, so that this dissertation is going to collect those narrations and trying to cover all ways and predications in which those hadiths are narrated as much as possible, in addition to arranging the critics views about them through mentioning discussions, judgements, differentiations and preferences among them as possible.
ماستر علوم الحديث
Keywords: روايات الأشعث,الحسن,السنن الكبرى, البيهقي; The novels of Al-Ash`ath, Al-Hasan, Al-Sunan Al-Kubra, Al-Bayhaqi